PENANAMAN NILAI PENDIDIKAN KARAKTER KEDISIPLINAN DALAM MENINGKATKAN PRESTASI SISWA KELAS V MI NU 24 SELOKATON - Fikarotal Ulya, Arina (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2023)
National education functions to develop abilities and shape the character of a dignified national civilization in order to make the nation's life more intelligent. Character education has become an important part of the development of education throughout the world. The research aims to increase understanding of the important role of character education in improving learning achievement, as well as provide guidance for educators, parents, and other stakeholders to be more effective in forming a young generation that excels academically and morally. This research uses descriptive and qualitative research methods. Students at MI NU 24 Selokaton are taught discipline in managing their time well in learning activities and discipline in various things. Students at this school are trained to be disciplined by obeying rules. Information was obtained that the role of teachers in this school has been going well. Apart from instilling the importance of discipline, teachers also apply discipline to learning